Student’ Perceptions of Healthy Snacks in School - Widyastuti, Suciati Rahayu; Kurniawan, Fajar; Kadiman, Kadiman; Octavia, Nurul (Jurnal Ilmu Keolahragaan, 2024)
Food safety, especially the use of hazardous chemicals, remains a major problem in Indonesia. The wide selection of packaged snacks available at schools makes it easier for children to obtain snacks without considering whether they are healthy or not. This study aims to determine students' understanding of healthy snacks in the school environment. The research method used is descriptive research with a survey type and quantitative approach. The research population consisted of 70 students. The entire population was used as a sample using saturated sampling technique. The instrument and data collection technique used a questionnaire. The data analysis technique used descriptive statistics in the form of percentages. The results of data analysis and discussion led to the following conclusions. The level of students' perception of healthy snacks at school showed that 17 students (24.3%) were in the high category, 41 students (58.6%) were in the medium category, and 12 students (17.1%) were in the low category. The conclusion is that students' perceptions of healthy snacks at SD Negeri 1 Kaduela are in the moderate category. This means that students' perceptions of healthy snacks at SD Negeri 1 Kaduela, which should contribute to efforts to promote a healthy lifestyle among students, are not yet optimal.